2000
DOI: 10.1097/00006676-200011000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species Activate Mitogen-Activated Protein Kinases in Pancreatic Acinar Cells

Abstract: It has been recently reported that kinases that belong to the mitogen-activated protein kinase (MAPK) family are rapidly activated by cholecystokinin (CCK) in rat pancreas both in vitro and in vivo. It is known that reactive oxygen species (ROS) play an important role in the pathogenesis of acute pancreatitis induced by supraphysiologic stimulation with CCK analogue, cerulein. The aim of our study was to evaluate whether MAPKs are activated by ROS in pancreatic acini. The activity of MAPK, c-Jun amino-terminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 42 publications
2
56
0
Order By: Relevance
“…MAPKs are mammalian serine/threonine protein kinases known to amplify signals involved in differentiation, inflammation, and apoptosis (Robinson & Cobb, 1997). P38 MAPK and JNK/SAPK (c-Jun N-terminal kinase/stressactivated protein kinase) are stress-responding MAPKs which induce inflammatory pathways in the early pathogenesis of severe AP (Dabrowski et al, 2000;Samuel et al, 2003). In this study, severe AP was induced through retrograde infusion of a 5% sodium taurocholate solution via the pancreatic duct at 100 uL/min.…”
Section: Activated Protein C In Apmentioning
confidence: 99%
“…MAPKs are mammalian serine/threonine protein kinases known to amplify signals involved in differentiation, inflammation, and apoptosis (Robinson & Cobb, 1997). P38 MAPK and JNK/SAPK (c-Jun N-terminal kinase/stressactivated protein kinase) are stress-responding MAPKs which induce inflammatory pathways in the early pathogenesis of severe AP (Dabrowski et al, 2000;Samuel et al, 2003). In this study, severe AP was induced through retrograde infusion of a 5% sodium taurocholate solution via the pancreatic duct at 100 uL/min.…”
Section: Activated Protein C In Apmentioning
confidence: 99%
“…It has been recently reported that p38 MAP kinase was activated in pancreatic acini by H 2 O 2 and menadione (Dabrowski et al, 2000). Therefore, the effect of H 2 O 2 on p38 MAP kinase was also examined in cultured ISMC.…”
Section: Characterization Of H 2 O 2 -Induced Map Kinase Activation Imentioning
confidence: 99%
“…To confirm that PKC is not involved in H 2 O 2 -induced ERK activation in ISMC, the effects of 3-[1-(dimethylaminopropyl)indol-3-yl]-4-(indol-3-yl)maleimide hydrochloride (GF109203X) (Dabrowski et al, 1997(Dabrowski et al, , 2000, a relatively specific PKC inhibitor, were also examined. Pretreatment of ISMC with 20 M GF109203X for 40 min had no effect on ERK activation by H 2 O 2 (Fig.…”
Section: Characterization Of H 2 O 2 -Induced Map Kinase Activation Imentioning
confidence: 99%
See 1 more Smart Citation
“…An in-vitro experiment showed that cytokine expression of acinar cells was mediated by two separate signal pathways, i.e, NF-κB and p38 MAP kinase. of which p38 MAP kinase is now suggested to play a major role [22][23][24][25][26][27] . The definitive role of these intracellular signaling cascades may lead to new designs for cytokine modulation therapy.…”
Section: Introductionmentioning
confidence: 99%